Dynamic study of a stochastic Holling III predator-prey system with a prey refuge. Issue 3 (2022) - Zhang, Yuke; Meng, Xinzhu
Abstract: Based on the truth that creatures in nature are concerned about environmental noise, we establish a stochastic Holling III predator-prey system with a prey refuge. In this stochastic system, the well-posedness of the system is investigated. For the extinction and persistence in mean, the threshold conditions are given in the next. Furthermore, the stochastic persistence of the system is also proved. At last, the main results are verified through numerical simulations. Biologically, it is observed that white noise can suppress the survival of populations.